Phyto-quantitative assessment and influence of Erythrophleum suaveolens extracts on Clarias gariepinus (Burchell, 1822) (Journal of the Bangladesh Agricultural University, 2020)
The study investigated phytotoxic effects of aqueous Erythrophleum suaveolens stem bark (AES) at 3.00, 2.25, 1.50 and 0.75 g/ L while leaf (AEL) at 3.50, 2.63, 1.75 and 0.88 g/ L extracts as treatments on 300 samples of Clarias gariepinus. Static non-renewal bio-assay test was used to determine the 96-hr acute toxicity while exposed the fish to 1/ 10th of LC50 for 28 days in sub-lethal tests. Results showed that tannins, saponins and oxalate were higher in AES while flavonoids, alkaloids, cyanogenic glycosides and phenols were higher in AEL. Levels of DO reduced in the treatments unlike in control, pH varied without changing the media slightly alkaline condition, Temperature was significantly different across the treatments, EC rose as levels of treatments increased more than in control. The TDS increased except at 2.63 g/ L and higher in the treatments than control. Occurrences of air gulping, discolouration, erratic swimming and resting at the bottom of the containers were alike as the concentrations of the extracts increased. The fish gained weight across the treatments and more in the AEL than AES; their 87.52 % and 96.41 %, respectively influenced LC50 of the fish. In conclusion, the AEL exhibited higher phytotoxic effect on the fish than aqueous E. suaveolens stem bark.J Bangladesh Agril Univ 18(2): 529–536, 2020https://doi.org/10.5455/JBAU.78025